Assistance for Home Industry Businesses in Bekasi for Digital Marketing Development and Packaging Design for Moristevia Tea: Pendampingan Usaha Industri Rumah Tangga Di Bekasi Untuk Pengembangan Marketing Digital Dan Desain Packaging Teh Moristevia - Deliyarti, Ida; Taryana, Nana; Herindiyati, Herindiyati; Widyawati, RA. Laksmi; Widyakusuma, Aryani; Herawati, Rahayu Triko (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The moringa industry has quite promising prospects. Currently, a Moristevia tea production business has been developed in Bumi Dirgantara Permai Housing, Jatisari Village, Jatiasih District, West Java Province, which is a Home Industry (IRT) business partner. From the results of the field study, it was found that the marketing business of Moristevia tea production was still using conventional methods, so its reach was limited. Another of that, the packaging display is not representative which results in the business experiencing stagnation. The aim of this Community Service is to increase the potential of the community, in this case the household business partners, to be more independent and productive. The implementation method has 3 stages there is preparation, implementation and evaluation stages. The stage of implementing marketing solutions and digital marketing training, namely designing the packaging for "Moristevia" tea products to be more attractive. The final result of the Digital Marketing mentoring and training activities is that Partner successfully registered the "Bakul Kelor Raya" Brand Account. The success of creating this account was on TikTok Ads, Instagram, Market Place, and WhatsApp Group